An An Analysis of Authentic Assessment Implementation in English Speaking Skill of Second Grade Students - Syafrizal, Syafrizal; Paharnzah, John; Nuraeni, Frasasti Wahyu (Journal of Research and Educational Research Evaluation, 2020)
This paper is a qualitative study which aimed at finding the result of authentic assessment implementation in assessing student English speaking skill. The data were analyzed using content analysis approach. The result of the study showed that the students in their speaking practice got various score in each category. In fluency category, there were five students or 16.67% got 5 score. It meant the student’s fluency and their volume is better. It was smooth and fluid speech. There were few or no hesitations and also there were not attempts to search for words. In pronunciation and accent category, the students who got 5 score was only two students or 7% which their pronunciation is excellent. They had good effort at accent like native. In vocabulary category, the students who got 5 score was 11 students or 37%. It meant their language control was excellent and there was a wide range of well-chosen vocabulary. In grammar category, there were only one student or 3.33% got 5 score. His/her grammatical structures are accuracy and variety. The last category was details which 16 students 53.33% got 5 score. It meant that their level of description was excellent. Additional details information beyond the required included. In the process of conducting evaluation, authentic assessment has big enough influence especially in assessing students’ speaking skill.